Family Decision-Making on International Migration - Till Nikolka; Panu Poutvaara (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We use a unique survey of Danes who have emigrated between 1987 and 2002 to study intra-family decision-making on international migration. Our survey reached 582 respondents with a Danish partner who was the same as before emigration. We model family decision-making in a bargaining framework and derive comparative statics to test with our data. Empirically, we find that family migration decisions are usually a shared preference, but that they are often driven to a larger extent by the male preference, most pronouncedly if the female is not college educated. Moreover, an increase in male wages goes along with relatively stronger male preferences towards joint emigration, which is in line with our theory.
Keywords: F22; J12; D13; 330